2023
DOI: 10.1161/jaha.122.028880
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen‐Related Receptor Gamma Gene Therapy Promotes Therapeutic Angiogenesis and Muscle Recovery in Preclinical Model of PAD

Abstract: Background Peripheral arterial disease and critical limb ischemia are cardiovascular complications associated with vascular insufficiency, oxidative metabolic dysfunction, and myopathy in the limbs. Estrogen‐related receptor gamma (ERRγ) has emerged as a dual regulator of paracrine angiogenesis and oxidative metabolism through transgenic mouse studies. Here our objective was to investigate whether postischemic intramuscular targeting of ERRγ via gene therapy promotes ischemic recovery in a preclini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…33 Nevertheless, gain-of-function studies using gene transfer have demonstrated that targeting ERRs is a viable therapeutic approach for mimicking exercise for vascular regeneration in PAD. 39 Multiple peroxisome proliferator activator receptor (PPAR) agonists (eg, cilostazol, GW0742, pioglitazone, pemafibrate, and fenofibrate) stimulate ischemic angiogenesis and/or prevent capillary regression in rodent models of hindlimb ischemia and diabetes. [40][41][42][43][44][45][46] These agents induce angiogenic stimulators including VEGFA and endothelial nitric oxide synthase (eNOS) in the ischemic muscle tissue.…”
Section: Nuclear Receptorsmentioning
confidence: 99%
“…33 Nevertheless, gain-of-function studies using gene transfer have demonstrated that targeting ERRs is a viable therapeutic approach for mimicking exercise for vascular regeneration in PAD. 39 Multiple peroxisome proliferator activator receptor (PPAR) agonists (eg, cilostazol, GW0742, pioglitazone, pemafibrate, and fenofibrate) stimulate ischemic angiogenesis and/or prevent capillary regression in rodent models of hindlimb ischemia and diabetes. [40][41][42][43][44][45][46] These agents induce angiogenic stimulators including VEGFA and endothelial nitric oxide synthase (eNOS) in the ischemic muscle tissue.…”
Section: Nuclear Receptorsmentioning
confidence: 99%